Ethical challenges in nephrology: a call for action - Martin, Dominique E; Harris, David C H; Jha, Vivekanand; Segantini, Luca; Demme, Richard A; Le, Thu H; McCann, Laura; Sands, Jeff M; Vong, Gerard; Wolpe, Paul Root; Fontana, Monica; London, Gerard M; et al. (Nature reviews. Nephrology, 2020)
The American Society of Nephrology, the European Renal Association-European Dialysis and Transplant Association and the International Society of Nephrology Joint Working Group on Ethical Issues in Nephrology have identified ten broad areas of ethical concern as priority challenges that require collaborative action. Here, we describe these challenges - equity in access to kidney failure care, avoiding futile dialysis, reducing dialysis costs, shared decision-making in kidney failure care, living donor risk evaluation and decision-making, priority setting in kidney disease prevention and care, the ethical implications of genetic kidney diseases, responsible advocacy for kidney health and management of conflicts of interest - with the aim of highlighting the need for ethical analysis of specific issues, as well as for the development of tools and training to support clinicians who treat patients with kidney disease in practising ethically and contributing to ethical policy-making.